Some words on knowledge - Hoop, Delpha May (My University, 1891)
Introduction: For years of hard and almost ceaseless study, and for what? We have had the book of nature opened wide enough for us to take a peep at some of her wonders as disclosed in botany, entomology, zoology, geology; mathematics means something more to us now than a simple or it may be intricate combination of numbers; we see in the history of individuals and of nations, not a mere succession of facts, but an illustration of the wonderful law of cause and effect; government is no longer a machine, but an embodiment of principles founded upon the general welfare of the governed; the rules of language are found to have reason for their basis; and above and beyond all we better understand the possibilities of the human mind, and know better how to seek the end of human existence. We have been shown how to work and well started upon any live of study or work on one may wish to pursue. But this one thing each graduate values most is the general knowledge and training he receives from his association with teachers and students.
Citation: Hoop, Delpha May. Some words on knowledge. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Education; Teacher; Knowledge; Studying; College; Theses; Manuscripts (documents)